2021
DOI: 10.1177/17448069211011326
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between spinal microgliosis and long-term development of tactile hypersensitivity in two different sciatic nerve crush injury

Abstract: Microglia activation following peripheral nerve injury has been shown to contribute to central sensitization of the spinal cord for the development of neuropathic pain. In a recent study, we reported that the amount of nerve damage does not necessarily correlate with chronic pain development. Here we compared the response of spinal microglia, using immunohistochemistry as a surrogate of microglial activation, in mice with two different types of crush injury of the sciatic nerve. We confirmed that incomplete cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…Astrogliosis, marked by increased cell volume and numbers, was prominent during chronic pain development, with microgliosis primarily implicated in pain initiation rather than maintenance. This was consistent with other studies showed the microglia activation generally precedes and subsides prior to astrocytes activation [ 22 , 29 , 30 ]. Indicating that microglia and astrocytes have separate roles in the induction, maintenance and resolution of chronic pain, with the initiation involves microgliosis while later phase involves astrogliosis.…”
Section: Discussionsupporting
confidence: 93%
“…Astrogliosis, marked by increased cell volume and numbers, was prominent during chronic pain development, with microgliosis primarily implicated in pain initiation rather than maintenance. This was consistent with other studies showed the microglia activation generally precedes and subsides prior to astrocytes activation [ 22 , 29 , 30 ]. Indicating that microglia and astrocytes have separate roles in the induction, maintenance and resolution of chronic pain, with the initiation involves microgliosis while later phase involves astrogliosis.…”
Section: Discussionsupporting
confidence: 93%
“…On day 1, when IL-1β expression already reached its maximum, we observed only a low level of microgliosis. This became evident on post-operative day 3 and—in line with observations from other laboratories [ 51 , 52 ]—fully developed on day 7. At this time point, NLRP3 was already upregulated in microglia as well; however, it did not colocalize with ASC, while IL-1β expression decreased to almost control levels, suggesting absence of inflammasome assembly in these cells.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously shown the development of a slow-onset mechanical hypersensitivity in a mouse model of "partial" sciatic nerve crush that does not appear after a more severe "full" crush injury. 23,50 This suggests the presence of an inflection point in the relationship between injury severity and the outcome of positive and negative sensory symptoms that challenges previous assumptions of clinical nerve injuries. 18 Here, we report a comprehensive behavioral and anatomical exploration of the partial and full sciatic nerve crush models at acute (2-7 days) and chronic (.30 days) time points in adult mice of both sexes using a simple and reproducible tool.…”
Section: Introductionmentioning
confidence: 94%
“…We have previously shown the development of a slow-onset mechanical hypersensitivity in a mouse model of “partial” sciatic nerve crush that does not appear after a more severe “full” crush injury. 23,50 This suggests the presence of an inflection point in the relationship between injury severity and the outcome of positive and negative sensory symptoms that challenges previous assumptions of clinical nerve injuries. 18…”
Section: Introductionmentioning
confidence: 96%